Increased IL-3 serum levels in chronic patients with schizophrenia: Associated with psychopathology. Issue 1 (30th September 2015) - Xiu, Mei Hong; Lin, Chong Guang; Tian, Li; Tan, Yun Long; Chen, Jing; Chen, Song; Tan, Shu Ping; Wang, Zhi Ren; Yang, Fu De; Chen, Da Chun; Zhang, Xiang Yang
Abstract: Schizophrenia is associated with the inflammation-related pathways, including aberrant cytokines levels. In this study, we examined the association of serum IL-3 levels with psychopahological symtoms in chronic schizophrenia. Serum IL-3 levels were assessed in 42 patients diagnosed with schizophrenia and compared to 43 healthy control subjects matched for age and gender. Schizophrenia symptomatology was assessed with the Positive and Negative Syndrome Scale (PANSS), and serum IL-3 levels were measured by sandwich enzyme-linked immunosorbent assay (ELISA). Our results showed that IL-3 levels were significantly increased in patients with chronic schizophrenia compared to healthy control subjects. Correlation analysis revealed a significant positive correlation between the IL-3 levels and the PANSS general subscore. Moreover, IL-3 levels were significantly positively correlated with depressive subscore. Our results suggested that IL-3 related pathway is associated with psychopathology of schizophrenia patients. Highlights: Serum IL-3 levels were measured in 42 patients and 43 healthy controls. IL-3 levels were significantly higher in patients than in controls. IL-3 showed significantly positive association with PANSS general subscore and depressive subscore. IL-3 related pathway may be involved in the psychopathology of schizophrenia patients.